Evapotranspiration estimation using a normalized difference vegetation index transformation of two satellites data in arid mountain areas - Almhab, Ayoub; Busu, Ibrahim (2008)
Evapotranspiration (ET) was estimated using a normalized difference vegetation index (NDVI) of satellite data on central Yemen Mountains. A procedure was developed which equated the index to crop coefficients. Evapotranspiration estimates for fields for three dates of Landsat Thematic Mapper data were highly correlated with ground estimates. Service area estimates using landsat Thematic Mapper (TM) and NOAA Advanced Very High Resolution Radiometer (AVHRR) data agreed well with estimates based on National Water Resources Authority (NWRA) gauging station data. Comparisons of ET results with traditional ET models show good agreement. Sensitivity analyses show that the model is accurate even without atmospheric correction.